ALMANAC: Internet of Things for Smart Cities - Bonino, Dario; Alizo, Maria Teresa Delgado; Alapetite, Alexandre; Gilbert, Thomas; Axling, Mathias; Udsen, Helene; Soto, Jose Angel Carvajal; Spirito, Maurizio (2015 3rd International Conference on Future Internet of Things and Cloud, 2015)
Smart cities advocate future environments where sensor pervasiveness, data delivery and exchange, and information mash-up enable better support of every aspect of (social) life in human settlements. As this vision matures, evolves and is shaped against several application scenarios, and adoption perspectives, a common need for scalable, pervasive, flexible and replicable infrastructures emerges. Such a need is currently fostering new design efforts to grant performance, reuse and interoperability while avoiding knowledge silos typical of early efforts on similar top is, e.g. Automation in buildings and homes. This paper introduces a federated smart city platform (SCP) developed in the context of the ALMANAC FP7 EU project and discusses lessons learned during the first experimental application of the platform to a smart waste management scenario in a medium-sized, European city. The ALMANAC SCP aims to integrate Internet of Things (IoT), capillary networks and metro access networks to offer smart services to the citizens, and thus enable Smart City processes. The key element of the SCP is a middleware supporting semantic interoperability of heterogeneous resources, devices, services and data management. The platform is built upon a dynamic federation of private and public networks, while supporting end-to-end security and privacy. Furthermore, it also enables the integration of services that, although being natively external to the platform itself, allow enriching the set of data and information used by the Smart City applications supported.